2019
DOI: 10.20452/pamw.15064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of air pollution on the number of hospital admissions for acute coronary syndrome in elderly patients (BIA – ACS Registry)

Abstract: Poland are cardiovascular diseases. A well-known risk factor for the development of these diseases is air quality. 7 The first incident of mass illness reported due to air pollution was the Meuse Valley fog. The city of Liège in Belgium evolved as a center for chemical industries since the beginning of the industrial revolution. In early December 1930, a very thick fog was observed in this area, which led to respiratory insufficiency among the local residents. Within 3 days, several thousand inhabitants were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…In addition, flue gas particles from engines often have volatile organic compounds adhered to them, which lead to the derangement of the atherosclerotic plaque. The formation of reactive oxygen species induced by air pollution may disturb vasodilation through NO, and it was also demonstrated that oxidative stress is primarily caused by the surface compounds adhering to the particulate matter [10,28,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, flue gas particles from engines often have volatile organic compounds adhered to them, which lead to the derangement of the atherosclerotic plaque. The formation of reactive oxygen species induced by air pollution may disturb vasodilation through NO, and it was also demonstrated that oxidative stress is primarily caused by the surface compounds adhering to the particulate matter [10,28,34].…”
Section: Discussionmentioning
confidence: 99%
“…The city of Bialystok has the 10th largest population in Poland and is characterized by lower SDR when compared to other major polish cities [ 24 ]. This suggests that the city itself, or Podlaskie Voivodeship on the whole, has a positive impact on the life expectancy of its residents, thanks to the abundant green areas and low level of industrialization, which leads to lower environmental pollution, and in particular better air quality, as compared to other regions [ 10 ]. However, the higher average age of the population predisposes them to the harmful effects of air pollutants [ 10 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional pilot study in India reported a higher prevalence of the symptoms of angina pectoris and cardiovascular diseases with an increased level of ambient air pollutants [ 40 ]. Another study evaluating the influence of ambient air pollution on the number of hospital admissions for acute coronary syndrome in elderly patients reported that a 10 μg/m 3 increase in PM 10 was associated with an increase in the number of hospitalizations due to unstable angina [ 41 ]. A study in Sao Paulo, Brazil, also observed that an interquartile range increase in CO was associated with a corresponding daily increase in angina or acute myocardial infarction room visits (6.4%, 95% CI: 0.7 to 12.1) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extreme temperature, change in weather condition, and air pollution have been found to be associated with an increased risk of MI. [7][8][9] The toxic effect of pollutants has been found to be higher during summer, thereby increasing the risk of cardiopulmonary diseases. 10,11 In Tamil Nadu, this study was conducted in the month of April, which is summer with daytime temperature generally above 30 C and nighttime temperature going down up to 25 C. During the COVID-19 lockdown period, cases of injuries, infections, illnesses related to behavior, and so on, have reduced in private and government hospitals in the state of Tamil Nadu.…”
Section: Discussionmentioning
confidence: 99%